Analysis Of Factors That Influence the Interest in Saving in Islamic Banks in Muhammadiyah University Students Yogyakarta - Danuarta, Arya Dwi; Wiranatakusuma, Dimas Bagus; Nurulhuda, Muhammad Farras Haykar (Universitas Muhammadiyah Yogyakarta, 2023)
Islamic banks are currently preferably chosen by public in storing assets or in banking activities over conventional banks. This study aims to reveal students' interest in saving and the factors influence students' interest in saving in Islamic banks. This research uses a qualitative method that involves interviews with students of Universitas Muhammadiyah Yogyakarta who store assets and carry out banking activities at Islamic banks. The findings can be interpreted that students choose banking activities at Islamic banks because of good services the banks provide, namely the easiness to access, available mobile banking, and in accordance with Islamic principles that avoid usury, gharar, maysir, haram and unjust. The factors that influence students to save in Islamic banks are service factors, Islamic factors, and needs factors.